Multiple-Body Collision Algorithms for Computational Simulation of High-Speed Air-Delivered Systems (Communications in Computational Physics, 2020)
Currently, there exists a lack of confidence in the computational simulationof multiple body high-speed air delivered systems. Of particular interest is the abilityto accurately predict the dispersion pattern of these systems under various deploymentconfigurations. Classical engineering-level methods may not be able to predictthese patterns with adequate confidence primarily due to accuracy errors attributableto reduced order modeling. In the current work, a new collision modeling capabilityhas been developed to enable multiple-body proximate-flight simulation in theLoci/CHEM framework. This approach maintains high-fidelity aerodynamics and incorporatessix degrees of freedom modeling with collision response, and is well-suitedfor simulation of a large number of projectiles. The proposed simulation system isintended to capture the strong interaction phase early in the projectile deployment,with subsequent transfer of projectile positions and flight states to the more economicalengineering-level methods. Collisions between rigid bodies are modeled using animpulse-based approach with either an iterative propagation method or a simultaneousmethod. The latter is shown to be more accurate and robust for cases involvingmultiple simultaneous collisions as it eliminates the need to sort and resolve the collisionssequentially. The implementation of both the collision detection methodologyand impact mechanics are described in detail with validation studies to demonstratethe efficiency and accuracy of the developed technologies. The studies chronologicallydetail the findings for simulating simple impacts and collisions between multiplebodies with aerodynamic interference effects.